Manajemen Anestesi pada pasien Abses serebri dengan Tetralogy of Fallot: Sebuah Laporan Kasus - ANNISA; Ari Wahyuni (CV. Jasa Sukses Abadi, 2022)
Tetralogy of Fallot is a congenital heart defect consisting of pulmonary valve stenosis, ventricular septal defect, right aortic valve deviation (overriding aorta), and right ventricular hypertrophy. TOF abnormalities constitute 7%-10% of congenital heart defects. The incidence is 0.23-0.63 cases per 1000 births. Tetralogy of Fallot is a congenital heart defect which is one of the most common cyanotic heart defects. The incidence of cerebrovascular disorders and brain abscess in TOF patients were 9.6% and 13.7%, respectively. In patients with tetralogy of Fallot who require surgery, it is important to know the proper anesthetic management. The goal is to perform anesthetic management according to the patient. The study conducted is a case report. Data were obtained through alloanamnesis and physical examination of patients. Assessment based on interview diagnosis and observation. A female patient aged 40 years came with complaints of decreased consciousness, vomiting and no appetite since 4 days ago. Previously, the patient had a history of VP Shunt insertion surgery 1 month ago due to hemorrhagic stroke. On physical examination, the general condition appeared to be severe, apathetic consciousness. On examination of the thorax and heart, abnormalities were found in the form of widening of the heart boundaries. On the superior and inferior extremities clubbing of fingers was found. Neurological examination revealed left limb weakness and motor speech disturbances. The patient underwent a craniotomy with prior anesthesia considerations. Preoperative, intraoperative, and postoperative management makes the success of surgery better